Sickness absence, presenteeism and work-related characteristics - Daniel Timo Arnold; Marco de Pinto (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper investigates how changes in work-related factors affect workers' absence and presenteeism behavior. Previous studies (implicitly) assume that there is a substitutive relationship - specifically, that a change in a work-related factor that decreases the level of absence simultaneously increases presenteeism (or vice versa). We set up a theoretical model in which work-related characteristics not only affect a worker's absence decision but also the critical level of sickness that defines presenteeism. Our model shows that non-substitutive relationships between absence and presenteeism are also conceivable. Using European cross-sectional data, we find only one substitutive and few complementary relationships, while the bulk of the work-related characteristics are related only to one of the two sickness states.
Keywords: J22; I10; M50; 330